Kapitālisma tirgus ekonomikas evolūcija un sadarbības ekonomikas attīstība. - Hames, Axelle Bonnie Ebene (Latvijas Universitāte, 2016)
Appelé par certain la Grande Récession, les pays industrialisés sont incapables de retrouver un niveau de croissance satisfaisant depuis 2008. Le modèle capitalisme ne semble plus répondre aux exigences économiques et sociales comme il l’a très bien fait pendant la période d’industrialisation. Parmi les nombreux modèles émergents, l’économie collaborative semble pertinente. Ce modèle redonne du sens à l’économie via une organisation horizontale et les principes de responsabilité sociétale, d’accessibilité, de progrès, de responsabilisation des usagers et de réputation qu’elle prône.

Since 2008, the industrialized countries are unable to reach back a satisfying level of wealth. If capitalism used to answer to the economic and social requirements during the industrialization period, though it probably has changed. Indeed unemployment rate has increased while the growth is lower. Among the many emerging models, collaborative economy seems to be relevant. This model recreates meaning in the economy thanks to a horizontal organization and the advocation of the principle of social responsibility, accessibility, progress, empowerment and reputation.
The evolution of the capitalist market economy and the development of collaborative economy.
Keywords: Vadībzinātne